Pemberdayaan UMKM Menuju Ekonomi Digital melalui Kuliah Kerja Nyata di Desa Cibeuteng Muara RT03/RW03 Kabupaten Bogor: Penelitian - Ridwan Baehaqi; Virgiawan Listanto; Adinda Febriana Putri; Viera Putri Septianti; Muhammad Raihan; Desta Anggre Nadia Zira; Farid Mubram Keliobas; Anton Wibowo; Berlianingsih Kusumawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Internal Community Service Program (KKN) 2024 organized by Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta is a mandatory program that students must complete to fulfill graduation requirements. This program aims to develop Micro, Small, and Medium Enterprises (MSMEs) in Cibeuteng Muara Village, particularly in Rt03/Rw03, Bogor Regency. The KKN was carried out in Cibeuteng Muara Village, Rt03/Rw03, Bogor Regency. The program aims to enhance the capacity of MSME actors through training on the use of digital technology such as social media, e-commerce, and business management applications to expand markets and improve operational efficiency. The KKN was conducted over eight meetings from September 12–29, with implementation methods including observation, interviews, material delivery, and documentation. The results of this program showed an increase in the knowledge and skills of MSME actors in utilizing digital technology. This activity is expected to serve as a sustainable model for MSME empowerment, support local economic growth, and prepare communities to face the challenges of the digital era. The program also provided valuable experience for students in integrating theory and practice, while at the same time supporting the vision of ITB Ahmad Dahlan as a socio-technopreneurship campus.